Enzymatic Digestion and Selective Quantification of Underivatised Delta-9-Tetrahydrocannabinol and Cocaine in Human Hair Using Gas Chromatography-Mass Spectrometry - Salah Eddine Breidi; James Barker; Andrea Petróczi; Declan P. Naughton (Journal of Analytical Methods in Chemistry)
Gas chromatography-mass spectrometric (GC-MS) methods for drug analysis routinely employ derivatising reagents. The aim of this paper was to develop a method for the analysis of two recreational drugs, delta-9-tetrahydrocannabinol (Δ9-THC) and cocaine in hair samples using GC-MS, without prior derivatisation, thus allowing the sample to be reanalysed in its original form. An enzymatic digestion technique was also developed. Ten hair samples, that were known positive for either Δ9-THC and/or cocaine, were enzymatically digested, extracted, and then analysed by GC-MS. All samples measured contained Δ9-THC and one sample contained cocaine. The limits of detection (LOD) and quantification (LOQ) were 0.02 ng/mg and 0.05 ng/mg, respectively, for cocaine and 0.015 ng/mg and 0.02 ng/mg, respectively, for Δ9-THC. The wide detection window, ease of direct analysis by GC-MS, lower detection limits of underivatised samples, and the stability of drugs using this technique may offer an improved method of analysis.